2020
DOI: 10.3390/ani10111962
|View full text |Cite
|
Sign up to set email alerts
|

The Relevance of Caseous Lymphadenitis as a Cause of Culling in Adult Sheep

Abstract: Four hundred and ninety-eight culled sheep received at the Ruminant Clinical Service of the Veterinary Faculty of Zaragoza, Spain, were examined in life and after humanitarian sacrifice in order to reach the final diagnosis of the cause of culling and to evaluate the presence of caseous lymphadenitis (CLA) lesions. One hundred and forty-seven of the 498 studied animals (29.52%) showed CLA compatible lesions that were subsequently confirmed by Corynebacterium pseudotuberculosis isolation. One hundred and seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 35 publications
(78 reference statements)
1
8
0
Order By: Relevance
“…CLA is a chronic infectious disease of a wide range of mammalian species in the world, including Ethiopia, characterized by the enlargement of one or more lymph nodes (Ali et al, 2016;Belchior et al, 2009;Braga, 2007;Ruiz et al, 2020). This study reported a single case of CLA out of 30 cattle slaughtered in the Bishoftu municipal abat- 2020) and Zeru and Kahsay (2014) that recorded a high occurrence of CLA in small ruminants.…”
Section: Discussionmentioning
confidence: 70%
“…CLA is a chronic infectious disease of a wide range of mammalian species in the world, including Ethiopia, characterized by the enlargement of one or more lymph nodes (Ali et al, 2016;Belchior et al, 2009;Braga, 2007;Ruiz et al, 2020). This study reported a single case of CLA out of 30 cattle slaughtered in the Bishoftu municipal abat- 2020) and Zeru and Kahsay (2014) that recorded a high occurrence of CLA in small ruminants.…”
Section: Discussionmentioning
confidence: 70%
“…Among the remaining microorganisms and parasites, many are more likely to be animal The main symptom of pseudotuberculosis is the enlarged and firm lymph nodes with purulent lymphadenitis, [4][5][6] while the subcutaneous abscess in the study was usually free of lymph node lesions. Lactococcus garvieae was first found in bovine mastitis, 7 and can also be isolated from diseased fish.…”
Section: Discussionmentioning
confidence: 83%
“…e prevalence of the disease in the individual level of dairy cows in Australia and the US is 22% and 75.8%, respectively. [23,24] e prevalence of the disease in the sheep and goat population in Europe is estimated at 72.79%. [23] e situation of JD prevalence in Iran showed higher infection compare to developed countries that have regular monitoring schedule and control in herds' level.…”
Section: Discussionmentioning
confidence: 99%
“…[23,24] e prevalence of the disease in the sheep and goat population in Europe is estimated at 72.79%. [23] e situation of JD prevalence in Iran showed higher infection compare to developed countries that have regular monitoring schedule and control in herds' level. Herd reservoir milk has 59% [25] and individual cow milk has 30%.…”
Section: Discussionmentioning
confidence: 99%